"I hope I'll outlive him": A qualitative study of parents' concerns about being outlived by their child with profound intellectual and multiple disabilities. Issue 2 (3rd April 2022) - Kruithof, Kasper; Olsman, Erik; Nieuwenhuijse, Appolonia; Willems, Dick
ABSTRACT: Background: The life expectancy of people with profound intellectual and multiple disabilities (PIMD) is increasing and parents express concerns about being possibly outlived by their child with PIMD. However, little is known about the nature of these concerns. Method: We interviewed 27 parents of persons with PIMD and analysed the data thematically, to explore parents' concerns about being outlived by their child. Results: Most parents hoped to outlive their child with PIMD and related this to the expectation of a decreased quality of life (QoL) of their child, when they would have passed away. The uncertainty about who would fulfil their parental roles in the future contributed to parents' concerns and sometimes resulted in feelings of despair. Conclusions: Our study provides insight into the nature and gravity of parents' concerns. The division of parents' concerns into roles helps to address future care and support gaps for people with PIMD.